Relationship Between Evangelism and Discipleship According ao Matthew 28:18-20 in Class XI Science Students of Immanuel High School Medan - Yona Gulo (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the significant relationship between evangelism and discipleship of science students of SMA Immanuel Medan. This type of research is descriptive correlational, the population in this study were 41 science students of SMA Immanuel Medan while the sample in this study amounted to 41 people with a total sampling technique. The tool used in data collection was a questionnaire consisting of 28 items for valid evangelism 14 items while for valid discipleship 14 items, with 4 options before the questionnaire was used to test its validity and reliability. The results of the data analysis requirements test of evangelism of science students of SMA Immanuel Medan were normally distributed with the calculation of Xcount < Xtable (33.06 < 54.57). The normality data of discipleship of science students of SMA Immanuel Medan were normally distributed with the calculation of Xcount < Xtable (29.361<54.57). The results of the linearity test of evangelism data with discipleship are linear with the equation Y = 10.24 + 0.827 consulted with Ftable obtained Fh> Ft (54.57> 0.355). The tendency test of Evangelism of science students of SMA Immanuel Medan tends to be moderate (41%) and Discipleship of science students of SMA Immanuel Medan tends to be moderate (38.4%). The results of the product moment correlation test obtained rtable = 0.308, rcount = 1.956 and rcount > rtable (1.956> 0.308). This shows that there is a relationship between evangelism and discipleship according to Matthew 28:18-20 science students of SMA Immanuel Medan. To test the significance level of the two variables, a "t" test was carried out, obtained tcount 13.008 ttable 1.684 th > tt (13.008> 1.684). So this shows that there is a significant relationship between evangelism and discipleship according to Matthew 28:18-20 science students at Immanuel High School, Medan